2022
DOI: 10.1021/acs.jpcc.1c05750
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent EXAFS Measurements of the Pb L3-Edge Allow Quantification of the Anharmonicity of the Lead–Halide Bond of Chlorine-Substituted Methylammonium (MA) Lead Triiodide

Abstract: This article reports on studies of chlorine-substituted MAPbI 3 using combined temperature-dependent X-ray diffraction (XRD) synchrotron and Pb-L3 edge extended X-ray absorption fine structure (EXAFS) to analyze the anharmonicity of the lead−halide bond. The EXAFS parameters were described in the orthorhombic phase by an Einstein or T 2 -type behavior, which was then compared with the experimental EXAFS parameters of the tetragonal/cubic phase. In the orthorhombic phase, it was observed that the asymmetry of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…In contrast to mixing with iodine, no evidence of the miscibility gap was found for the mixed MAPb(Br 1−x Cl x ) 3 perovskites due to more similar radii of Br − and Cl − anions (196 pm vs 181 pm). 362364,368,369,377−382 Several studies observed cubic symmetry at room temperature for different compositions covering the whole mixing interval 364,380,381,383 in agreement with the symmetry of the end members (see Figure 3).…”
Section: X-site Mixing In 3d Perovskitesmentioning
confidence: 99%
“…In contrast to mixing with iodine, no evidence of the miscibility gap was found for the mixed MAPb(Br 1−x Cl x ) 3 perovskites due to more similar radii of Br − and Cl − anions (196 pm vs 181 pm). 362364,368,369,377−382 Several studies observed cubic symmetry at room temperature for different compositions covering the whole mixing interval 364,380,381,383 in agreement with the symmetry of the end members (see Figure 3).…”
Section: X-site Mixing In 3d Perovskitesmentioning
confidence: 99%
“…The change in the Pb–I bond distance observed from EXAFS is, however, inconsistent with almost no change in lattice constant observed from XRD. The local Pb–I bond distance was reported to be different from the XRD results depending on the composition of materials due to the different rigidities of Pb–halide octahedra . Thus, the local structure and the Pb–I bond distance obtained from EXAFS might provide different information, although it is incommensurable with the bulk lattice parameters.…”
mentioning
confidence: 99%
“…The local Pb−I bond distance was reported to be different from the XRD results depending on the composition of materials due to the different rigidities of Pb−halide octahedra. 31 Thus, the local structure and the Pb−I bond distance obtained from EXAFS might provide different information, although it is incommensurable with the bulk lattice parameters. The origin of the elongated Pb−I bond distance might be related to the thermally induced PbI 2 with a longer Pb−I bond distance of ∼3.28 Å than that in FAPbI 3 (3.18 Å).…”
mentioning
confidence: 99%